2007
DOI: 10.1001/archotol.133.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Recurrence and Mortality in Nonselective Cyclooxygenase Inhibitor Users

Abstract: To determine whether ongoing use of a cyclooxygenase (COX) inhibitor is associated with a reduction in mortality and disease recurrence after head and neck cancer treatment. Design: Retrospective case-control study. Patients: A total of 325 potential subjects with head and neck squamous cell carcinoma were identified using an electronic patient database. Main Outcome Measure: The rate of COX inhibitor use among patients who had died or whose disease had recurred (cases) was compared with the rate of use among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In a few clinical trials, administration of celecoxib as an adjuvant therapy has been associated with significant response rates (22, 31, 32). One retrospective study looking at the relationship between the use of non-selective cyclooxygenase inhibitors and overall survival in HNSCC patients found that median survival was increased among COX inhibitor users, although the regimen/type of COX inhibitor use was not controlled for in this study (21). A critical gap remains in our knowledge of how COX inhibition impacts on the T cell responses in HNSCC patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a few clinical trials, administration of celecoxib as an adjuvant therapy has been associated with significant response rates (22, 31, 32). One retrospective study looking at the relationship between the use of non-selective cyclooxygenase inhibitors and overall survival in HNSCC patients found that median survival was increased among COX inhibitor users, although the regimen/type of COX inhibitor use was not controlled for in this study (21). A critical gap remains in our knowledge of how COX inhibition impacts on the T cell responses in HNSCC patients.…”
Section: Discussionmentioning
confidence: 79%
“…In several murine and hamster models of head and neck cancer, administration of the COX-2 inhibitor celecoxib decreased expression of vascular endothelial growth factor (VEGF) and survivin, increased tumor cell apoptosis and decreased tumor growth (1820). A few studies have shown clinical responses resulting from COX inhibition in HNSCC patients (21, 22). In a model of lung carcinoma, inhibition of COX-2 resulted in increased antitumor reactivity by shifting the cytokine balance of resident immune cells toward a more proinflammatory, Th1-like phenotype, as characterized by increased IL-12 production and decreased IL-10 production (23).…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical trials have been unable to show efficacy of celecoxib (a specific COX-2 inhibitor) [80] and Ketorolac (COX-1 and -2 inhibitor) [81] in inhibiting oral leukoplakia and oral premaligant lesions, respectively. Non-steroidal anti-inflammatory drugs (NSAIDs), a known PGE 2 inhibitor, had no effect on HNSCC recurrence or survival when compared to non-users in a retrospective case-control study [82]. Thus, COX-2 therapies may be most effective when used with other therapies.…”
Section: Sphk1 Influence In Head and Neck Cancermentioning
confidence: 99%
“…Twenty-one studies (two on all cancer sites, five on breast cancer, eight on colorectal cancer (CRC), one on head and neck cancer, one on pancreas cancer and four on prostate cancer) were identified that studied anti-inflammatory medications and cancer recurrence and cancer-specific mortality ( Table 4) [72,75,101,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132]. The drugs evaluated in the studies included all antiinflammatory drugs (i.e., aspirin, ibuprofen and COX inhibitors) and acetaminophen.…”
Section: Current Literaturementioning
confidence: 99%